Gerenciamento de requisitos no ambiente Cocar - Thommazo, André Di (Universidade Federal de São Carlos, 2008)
The objective of this work was to implement an initial version of a development support environment, based on the Use Case Model, named COCAR. The conception and the features of this environment are the result of several master papers. In the scope of this work, the main subject under study has been requirement management, although concerning its implementation, functionalities related to other previous works have also been contemplated. This environment prop up a few software development tasks, aiming at leveling up qualitity throughout the process. It is well know that one of the principal characteristics related to software product quality is that the product should meet the user requirements. In requirement engineering, the comunication between the user and the developer is stated in the Requirement Document and based on it, the requeriment can be modelled, for instance, by means of the Use Case Model. Despite the efforts invested in gathering requirements with the user, it is know that they are very likely to be ammended during the development process. A fundamental factor for the maintainance of the overall quality is that such modifications to the requirements occur in a monitored and foreseeable way. The ability to describe and follow a requirement life-cycle within the software development process is denominated requirement traceability. As the requirement document represents what binds the user and the developers, if traceability is obtained from that point onwards, the quality of the development process tend to increase and this permits monitoring since its earliest phases. This paper contribution to the implementation of the environment COCAR, includes features such as: registering the requirement of a system, generating of a Use Case Model, requirement management (mainly what concerns traceability between the Requirement Document and the Use Case Model), providing traceability metrics found in academic literature and the possibility of determining the relationship between the requirements. Based on the data provided by the tool, it is easy to perceive that they are highly relevant to any system development planning or following up, which can be an important pragmatic contribution to the improvement of software development and software products.
Keywords: Engenharia de requisitos; Gerenciamento de requisitos; Rastreabilidade de requisitos; Modelo de casos de uso; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO